AHP-consensus judgement on transitional decision-making: With a discussion on the relation towards open innovation - Mohd Fakhrur Razi Misran; Eida Nadirah Roslin; Nurhayati Mohd Nur (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Green and sustainable engineering business models have become a major topic across industries due to concerns regarding environmental issues and the decline of natural resources. Remanufacturing is showing promise as a preferable solution in terms of environmental, societal, and economic factors compared to alternatives such as repairing, reconditioning, and recycling. By considering the nature of the closed cycle loop system, this paper proposes the idea of a transitional agenda into remanufacturing. However, different countries should employ different approaches to such a transition in order to appropriately account for and integrate diverse stakeholders, perspectives, and preferences. Therefore, the main objective of this study is to evaluate prioritized elements and sub-elements in the development of a transitional decision-making framework (TDMF) in the Malaysian automotive industry by applying the analytical hierarchy process (AHP). Aggregation of individual and group judgement is done for prioritised elements and their sub-elements, which are then ranked accordingly using element weights based on the acceptance of individual and group consistency index values.
Keywords: 650; analytic hierarchy process; consistency; group decision making; remanufacturing; transitional